English phonology - Giegerich, Heinz J (Cambridge University Press, 1998)
The book deals principally with three varieties of English: "General American", Southern British "Received Pronunciation" and "Scottish Standard English". It offers a systematic and detailed discussion of the features shared by these major accents, and explains some major differences